Event-triggered control of discrete-time switched linear systems with network transmission delays. (January 2020) - Xiao, Xiaoqing; Park, Ju H.; Zhou, Lei; Lu, Guoping
Abstract: The event-triggered control problem for discrete-time switched linear systems with network transmission delays is investigated in this paper. It is assumed that the controller can only access the transmitted information of system state and mode at each event-triggered instant. A mode dependent event-triggered transmission scheme is proposed and the closed-loop system is modeled as a switched system with delayed state and augmented switching signal. Then based on the multiple Lyapunov functional method, an exponential stability condition and design method for state feedback controller gains are obtained. The proposed approach leads an important step to study the event-triggered control for discrete-time switched systems. Finally, the effectiveness and improvement of the proposed approach are illustrated by a numerical example.